Decontamination of select infrastructure materials after a radiological incident using a water-based formulation. (October 2018) - Semmler, Jaleh; Snaglewski, Anthony; Toor, Arshad; Khan, Zahid; Kuang, Wenxing; Volchek, Konstantin; Azmi, Pervez; Blinov, Vladimir; Brown, Carl
Abstract: This paper summarizes the results of the decontamination of the infrastructure materials concrete, limestone, brick and asphalt contaminated with 60 Co, 85 Sr, 137 Cs and 241 Am. The paper focuses on the effect of differences in substrate properties and of the pH of the radionuclide solution used for surface contamination on adsorption or ion exchange of the radionuclides and how these factors affect the decontamination effectiveness. A six-component chemical formulation was used and a process effectiveness of up to 76% was obtained depending on the substrate and radionuclide. Asphalt was the easiest material to decontaminate because of its more hydrophobic nature. Concrete and limestone (and to some extent brick) were less effectively decontaminated as their porous surfaces allowed penetration of radionuclides into water-filled pores in the substrate facilitating adsorption or ion exchange and making them difficult to remove. Brick was the most difficult material to decontaminate because the major component of brick is clay which retains most mono- and divalent ions. The removal of 60 Co, 85 Sr and 137 Cs from the surfaces of concrete, limestone and brick increased when the pH of the radionuclide solutions was moderately acidic to neutral compared to when they were highly acidic. The variability in the test results was similar to that observed in other studies using other decontamination methods, attributed to the inhomogeneity of the substrates used and considered representative of real infrastructure materials. Highlights: Select infrastructure materials contaminated by 60 Co, 85 Sr, 137 Cs and 241 Am were decontaminated with a water-soluble mixture. Substrate properties and radionuclide solution pH have a major effect on decontamination effectiveness. The greater hydrophobicity of asphalt surfaces make them easier to decontaminate. Porous surfaces are difficult to decontaminate because of radionuclide uptake in the subsurface layer. Clays retain some radionuclides and makes brick decontamination challenging.